Feed and fodder availability in Punjab state vis-a-vis livestock population -An estimate - TANWAR, P S; VERMA, H K (The Indian Journal of Animal Sciences, 2017)
The aim of present study was to estimate the feed and fodder demand for the existing livestock population and supply in Punjab. The study was based on secondary data collected from different sources. The livestock population were converted in to Adult Cattle Unit (ACU) on the basis of species, age and sex. The body weight of each ACU was considered 350 kg and dry matter consumption was assumed 2% of the body weight.The total adult cattle unit (ACU) in the state is 5.85 Million, which required 14.94 million tonnes feed and fodder on dry matter basis. The total annual availability of feed and fodder in the state was estimated 24.24 million tonnes against the requirement of 14.94 million tonnes and thereby excess of around 62.18% per annum. The availability of feed and fodders was excess in 18 districts except Amritsar and SAS, Nagar district of the state. Average dry matter availability in the state was 11.35 kg/ACU per day against requirement (7 kg). The policies to develop blocks of fodder in the state and transport to the deficit areas of the country need priority attention to solve the problem of fodder in deficit areas.